1996
DOI: 10.1253/jcj.60.767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Effects of the Beta-Blocking Agent Bisoprolol and the Calcium-Blocking Agent Diltiazem in Patients With Heart Failure Due to Dilated Cardiomyopathy

Abstract: Beta-blocking agents reduce mortality and improve symptoms in patients with dilated cardiomyopathy (DCM). There have been reports that diltiazem, a calcium-blocking agent, is also effective in such patients. We prospectively compared the effects of the beta-blocking agent bisoprolol with those of the calcium-blocking agent diltiazem in 18 patients (11 males and 7 females, age 14 to 68) with DCM. The 18 patients, (10 in New York Heart Association functional class III and 8 in class IV) were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…4 However, some studies have revealed that betablockers with ISA have no beneficial effect in patients with severe heart failure although they improve the clinical condition in mildly symptomatic patients. [9][10][11][12][13] The mechanism of the beneficial effect of beta-blocker treatment for heart failure remains unclear, but suppression of circulating cathecholamines leading to myocardial toxicity and myocardial dysfunction, restoration of -1-receptor downregulation and improvement of myocardial metabolism due to a reduction of heart rate and oxygen consumption have been postulated as possible mechanisms. 16 In a trial using various beta-blockers for heart failure, Swedberg et al indicated that alprenolol, nonselective and with ISA, caused deterioration in heart failure or provoked heart failure death, and had to be replaced by metoprolol without ISA for a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, some studies have revealed that betablockers with ISA have no beneficial effect in patients with severe heart failure although they improve the clinical condition in mildly symptomatic patients. [9][10][11][12][13] The mechanism of the beneficial effect of beta-blocker treatment for heart failure remains unclear, but suppression of circulating cathecholamines leading to myocardial toxicity and myocardial dysfunction, restoration of -1-receptor downregulation and improvement of myocardial metabolism due to a reduction of heart rate and oxygen consumption have been postulated as possible mechanisms. 16 In a trial using various beta-blockers for heart failure, Swedberg et al indicated that alprenolol, nonselective and with ISA, caused deterioration in heart failure or provoked heart failure death, and had to be replaced by metoprolol without ISA for a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%